THE EFFECT OF APPLYING SOCRATIVE ON STUDENTS’ READING ABILITY - Fatmawaty, Riryn; Sholihah, Sofi Nurhidayatus (Universitas Islam Lamongan, 2020)
This study aimed to determine the impact of the application of socrative to the reading ability of students in industrial 4.0 era, where anything was done using the internet and computers. The method used in this study was the pre-experimental type One Group Pretest-Posttest. This method used a class that was used as the object of research. This research was conducted at SMK 1 Baureno located on Jl. Raya Kepohbaru Department No. 258, Baureno, Plumbungan, Bojonegoro. The object of this research was the 10th grade computer and network engineering students at SMK 1 Baureno. The number of students was 34 consisting of 17 male students and 17 female students. This research was conducted on February 5 through March 11, academic year 2019/2020. There were three activities carried out, namely pretest, treatment and posttest. The hypothesis accepted in this study was the alternative hypothesis (Ha). Because the results of this study indicated that the t-test of 34 students was 17,07 with a significant level of t-table 0,05. This mean that there were differences in the ability of students before and after treatment was given. And from the results of questionnaires that had been done that 10th grade students of computer and network technique at SMK 1 Baureno prefered to read online (using socrative) rather than reading offline.Â Keywords: Reading, socrative